MEMBANGUN HARMONI: OPTIMALISASI FKUB SALATIGA DALAM MENGATASI KONFLIK KEAGAMAAN DAN MEMPERTAHANKAN KOTA TERTOLERANSI (2018–2023) - Abdoeh, Nor Mohammad (Departemen Sosiologi Aga,ma, Universitas Islam Negeri Alauddin Makassar, 2024)
The phenomenon of the harmony and tolerance survey that ranked Salatiga as the 2nd most tolerant city in 2018, then 1st in 2020, then 3rd in 2021 and 2nd in 2022, and 3rd in 2023, makes Salatiga City proud of itself. With Salatiga City being inaugurated as a city of tolerance amidst the rampant cases of intolerance in this country. The author is interested in examining more deeply how FKUB Salatiga optimizes the resolution of religious conflicts in Salatiga city. And how does FKUB Salatiga City maintain the top 10 most tolerant cities in Indonesia during 2018-2023? And what are the obstacles in realizing religious harmony in Salatiga City? This research is a descriptive field study using a sociological approach. The conclusion of this article is that the way to optimize FKUB Salatiga in resolving religious conflicts are: a) Conducting dialogue with religious leaders and community leaders. b) Further accommodating and conveying the aspirations of religious mass organizations. c) Conducting socialization of laws and policies in the field of religion. d) Providing written recommendations on the application for the establishment of houses of worship and the use of residential houses as temporary places of worship. e) Conducting research and field review related to the establishment of houses of worship. f) Deploying a team of field verifiers from FKUB from across religions to review administrative requirements. Furthermore, FKUB Salatiga's technique in maintaining the top 10 most tolerant cities is by emphasizing dialogue, socializing regulations, and synergizing religious and community leaders. The factors that become obstacles are: a) The Joint Regulation of the Minister of Religious Affairs and the Minister of Home Affairs has not been fully understood. b) The absence of a legal umbrella in the Joint Regulation of the Minister of Religious Affairs and the Minister of Home Affairs in accommodating sects in certain religions. c) The absence of a legal umbrella in the Joint Regulation of the Minister of Religious Affairs and the Minister of Home Affairs relating to the establishment of a funeral home for ethnic Chinese. d) Lack of coverage of suburban areas related to the problem of socialization of religious harmony. e) The community does not fully understand Law No. 5 of 2018 concerning Amendments to Law No. 15 of 2003 concerning the Stipulation of Government Regulations in Lieu of Law No. 1 of 2002 concerning Eradication of the Criminal Acts of Terrorism into Law.